Determinación de prevalencia de neosporosis bovina asociado a factores de riesgo en la provincia Bolívar - Gaibor Jiménez, Karla Paola (2019)
In this research, the prevalence of bovine neosporosis associated with risk factors in the Bolivar province was determined, so we considered; determine the prevalence of Bovine Neosporosis associated with risk factors in Bolivar Province, establish the existence and prevalence of Bovine Neosporosis, identify the risk factors that favor the presence of Bovine Neosporosis and finally perform the Geo-referencing of the properties positive to bovine Neosporosis. For the present investigation, the type of analysis used was a descriptive statistical model for which tests of analysis of means, percentages and frequencies were used, all this in relation to the factors under study that were components of risks in 545 cattle (females) distributed in 78 properties in the Province of Bolívar. The experimental results showed that the prevalence of Bovine Neosporosis per individual in the province was 19.08%; the prevalence of Bovine Neosporosis by property was 66.7%; the prevalence of Neosporosis per farm according to the type of farm was greater in small farms 1 (1-10 cows) with 63.46% of positives 33 of 52 positive and farm 2 (11 to 100 cows) presented 36.54 % 19 of 52 positive. Indicating that the cows that were most affected were the cows that are in the farms; the prevalence by positive animals according to the cantons was as follows: Caluma 11.53%, Chillanes 1.92%, Chimbo 4.80%, Echeandia 11.53% Guaranda 49.03% and San Miguel 21.15%; According to the intrinsic factors, it was determined that the numbers of deliveries and milk production are the risk factors that are related to the disease: the numbers of deliveries in all the categories presented high OR; with regard to milk production, it is indicated that the production cows from 1 to 10Lt were closely linked to the disease, which would indicate that the affected cows would have low milk production.